Acute Pancreatitis with Rapid Clinical Improvement in a Child with Isovaleric Acidemia. (4th February 2013) - Mantadakis, Elpis; Chrysafis, Ioannis; Tsouvala, Emmanouela; Evangeliou, Athanassios; Chatzimichael, Athanassios
Abstract : Isovaleric acidemia is a rare branched-chain organic acidemia. The authors describe a 3.5-year-old girl with isovaleric acidemia and acute abdominal pain associated with bilious emesis. Elevated serum amylase and abdominal ultrasonography demonstrating an enlarged and edematous pancreas, along with the presence of peripancreatic exudates, confirmed the presence of acute pancreatitis. The patient recovered quickly with intravenous hydration, pancreatic rest, and administration of intravenous L-carnitine. Pancreatitis should be ruled out in the context of vomiting in any patient with isovaleric acidemia. Conversely, branched-chain organic acidemias should be included in the differential diagnosis of any child with pancreatitis of unknown origin.